2018
DOI: 10.1186/s12885-018-4187-y
|View full text |Cite
|
Sign up to set email alerts
|

Time to diagnosis and associated costs of an outpatient vs inpatient setting in the diagnosis of lymphoma: a retrospective study of a large cohort of major lymphoma subtypes in Spain

Abstract: BackgroundMainly because of the diversity of clinical presentations, diagnostic delays in lymphoma can be excessive. The time spent in primary care before referral to the specialist may be relatively short compared with the interval between hospital appointment and diagnosis. Although studies have examined the diagnostic intervals and referral patterns of patients with lymphoma, the time to diagnosis of outpatient compared to inpatient settings and the costs incurred are unknown.MethodsWe performed a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Although there were no differences in the time to diagnosis between the 2 approaches, the costs of inpatients’ diagnosis were nearly the double than those of QDU patients. Because the high costs of hospitalization and the reported advantages for patients of a hospital-based ambulatory versus inpatient management, [ 15 , 17 ] an ambulatory instead of an inpatient diagnostic evaluation may be preferable in patients with suspected pancreatic cancer. However, it may be argued that admission has an added value for diagnosis since it is associated with issues which may not be properly treated or managed in an ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were no differences in the time to diagnosis between the 2 approaches, the costs of inpatients’ diagnosis were nearly the double than those of QDU patients. Because the high costs of hospitalization and the reported advantages for patients of a hospital-based ambulatory versus inpatient management, [ 15 , 17 ] an ambulatory instead of an inpatient diagnostic evaluation may be preferable in patients with suspected pancreatic cancer. However, it may be argued that admission has an added value for diagnosis since it is associated with issues which may not be properly treated or managed in an ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mostly owing to delayed investigations ordered by PC physicians, patients with suspected cancer, even with an appropriate performance status, have been traditionally hospitalized to speed-up diagnosis. [ 12 , 16 , 17 ] However, admission for diagnostic workup of such patients may only increase the costs of hospitalization, contributing to increased expenditures in healthcare. To avoid delays and potentially avoidable admissions, the Spanish healthcare system created in the 2000s hospital based-ambulatory facilities called quick diagnosis units (QDUs).…”
Section: Introductionmentioning
confidence: 99%
“…During this encounter, however, the inpatient lymph node biopsy was indicated due to generalized lymphadenopathy of unclear etiology and worsening clinical status [8]. A study has shown that inpatient excisional biopsies may lead to quicker diagnoses in hematologic disease, but outpatient ones are more cost-effective [9]. In immunocompromised patients, a high index of suspicion is required to prompt a full skin exam and potentially earlier inclusion of an excisional lymph node biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we can tell, there are no previous reports analyzing temporal trends including clinical characteristics and causes of hospitalizations for patients evaluated at quick diagnosis units. Evidence for the role of quick diagnosis units as an alternative ambulatory care model to inpatient admission comes mainly from level 2a and 2b studies, including two systematic reviews [11,33] and observational studies (prospective and retrospective) [16][17][18][19][20]24,25]. A systematic review reported in 2014 by independent US authors selected for final review four studies that focused on quick diagnosis units, of which three had been published in Spanish medical journals [33].…”
Section: Discussionmentioning
confidence: 99%
“…Different, mainly observational studies revealed that these units were as clinically effective as inpatient admission to reach a diagnosis, with similar diagnostic times. While patient reported satisfaction was also similar or higher than conventional hospitalization, quick diagnosis units proved cost-effective with associated costs significantly lower than the same costs applied to the evaluation of the same conditions in the hospital setting [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%